Effect of Mo content on microstructure and mechanical properties of WCoB-TiC based cermets. Issue 1 (February 2020) - Ke, Z; Zheng, Y; Sun, F; Zhang, G T; Zhang, J J; Xu, X Y; Wu, H; Dong, Z W; Zhou, W
Abstract: The effect of Mo content on microstructure and mechanical properties of WCoB-TiC based cermets fabricated by boronizing sintering reaction was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray analysis (EDX). Results showed that phase compositions of all the WCoB-TiC cermets with 0 to 20 wt% Mo addition were composed of W2 CoB2, TiC, TiB2, and the (211) diffraction peak of W2 CoB2 phase was continuously shifted towards a high angle with Mo content, indicating that (W, Mo)2 CoB2 solid solutions in cermets with 5-20 wt% were formed. Moreover, the cores of W2 CoB2 grains were enriched in Mo, while rims of W2 CoB2 grains had a relatively lower Mo content, resulting in the formation of a core/rim structure. As Mo content increased, the porosity gradually dropped, while the relative density continuously increased, due to the improved wettability of liquid phase in the hard phase. In addition, average grain sizes dropped initially and then rose gradually with Mo content. An increase in average grain sizes was due to the coalescence and growth of hard-phase particles. The WCoB-TiC cermet with an 10 wt% Mo addition showed excellent comprehensive mechanical properties with a transverse rupture strength of 815 MPa, a Rockwell hardness of 93.4 HRA, and a fracture toughness of 12.5 MPam 1/2, respectively.